2020
DOI: 10.3390/antibiotics9040147
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils of Aromatic Plants with Antibacterial, Anti-Biofilm and Anti-Quorum Sensing Activities against Pathogenic Bacteria

Abstract: Both the ability of bacteria to form biofilms and communicate through quorum sensing allows them to develop different survival or virulence traits that lead to increased bacterial resistance against conventional antibiotic therapy. Here, seventeen essential oils (EOs) were investigated for the antimicrobial, antibiofilm, and anti-quorum sensing activities on Escherichia. coli O157:H7, Escherichia coli O33, and Staphylococcus epidermidis ATCC 12228. All essential oils were isolated from plant material by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 48 publications
(49 reference statements)
1
56
1
3
Order By: Relevance
“…The scientific community is in agreement that the actions of these natural phytocomplexes depend not only on the compounds present in greater quantities but on the chemotype. Indeed, it is possible to find very powerful actions [ 42 , 43 ] but also phytocomplexes with much lower antimicrobial action [ 44 , 45 ]. The Thymus oil used contains predominantly phenolic monoterpenes ( Table 1 ) and maintains its antibacterial action even in the solid form by selectively acting on pathogenic bacteria ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The scientific community is in agreement that the actions of these natural phytocomplexes depend not only on the compounds present in greater quantities but on the chemotype. Indeed, it is possible to find very powerful actions [ 42 , 43 ] but also phytocomplexes with much lower antimicrobial action [ 44 , 45 ]. The Thymus oil used contains predominantly phenolic monoterpenes ( Table 1 ) and maintains its antibacterial action even in the solid form by selectively acting on pathogenic bacteria ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have documented the antibacterial effects of phenol-rich extracts commonly found in plants. These studies have highlighted the use of phenolic compounds to control pathogenic bacteria, including those with a commercial antibiotic resistance profile [ 18 , 19 ]. The antibacterial effects of phenolic compounds have also been primarily associated with the presence of hydroxyl groups in their molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Chelating agents, peptide antibiotics, lantibiotics, synthetic chemical compounds, and herbal active compounds are some examples of compounds that have been tested [ 145 , 146 ]. Within the plant-origin compounds, EOs were proved to be able to prevent the formation of biofilms [ 147 , 148 , 149 ]. The ability of EOs to inhibit microbial adherence and further biofilm development is associated by their capacity to disrupt the quorum sensing system (QS) [ 148 , 150 , 151 , 152 , 153 ].…”
Section: Superparamagnetic Iron Oxide Nanoparticles Supplemented Wmentioning
confidence: 99%
“…Within the plant-origin compounds, EOs were proved to be able to prevent the formation of biofilms [ 147 , 148 , 149 ]. The ability of EOs to inhibit microbial adherence and further biofilm development is associated by their capacity to disrupt the quorum sensing system (QS) [ 148 , 150 , 151 , 152 , 153 ]. QS is a largely distributed cell–cell communication process that has been identified not only in bacteria, but also in fungi, protozoa, and recently in bacteriophages [ 154 , 155 , 156 , 157 , 158 ].…”
Section: Superparamagnetic Iron Oxide Nanoparticles Supplemented Wmentioning
confidence: 99%